The downregulation of miR-519a predicts poor prognosis and contributes to tumor progression in gastric cancer - Cai, Huimei (Int J Clin Exp Pathol, 2019)
Introduction: MicroRNAs (miRNAs) have been demonstrated to be involved in the pathogenesis of various human cancers. However, the role of microRNA-519a (miR-519a) in gastric cancer (GC) remains unclear. This study aimed to investigate the clinical value and biological function of miR-519a in GC. Methods: The expression of miR-519a in GC tissues and cell lines was estimated by quantitative real-time polymerase chain reaction (qRT-PCR). A survival analysis for GC patients was performed using the Kaplan-Meier method. A Cox regression analysis was used to confirm the prognostic value of miR-519a. The biological function and potential targets of miR-519a in GC progression were assessed using cell experiments. Results: In this study, we found that miR-519a was an important tumor suppressor with downregulated expression in GC tissues and cells compared with the normal controls (all P < 0.05). MiR-519a expression was inversely correlated with differentiation, lymph node metastasis, and patients’ TNM stages. Decreased miR-519a expression was associated with the poor overall survival of GC patients (log-rank P = 0.002) and served as an independent prognostic biomarker for the patients. The in vitro analyses indicated that miR-519a overexpression in GC cells resulted in inhibited cell proliferation, migration and invasion, and IGFBP1 was determined to be a direct target of miR-519a. Conclusion: All the data in the present study revealed that the downregulated expression of miR-519a predicts the poor prognosis of GC and is involved in the regulation of GC progression. We consider that miR-519a may be a candidate therapeutic target for GC treatment.